Physiotherapy performance after treatment of telangectatic osteosarcoma with total endoprosthesis of the femur with acetabulum, knee joint and tibial componente: Case report (Research, Society and Development, 2024)
Objective: retrospective analysis of the functional results of a patient diagnosed with bone sarcoma in the distal end of the femur, who underwent reconstruction with a total knee endoprosthesis. Methodology: The article is an observational, retrospective and descriptive case report of a patient with osteosarcoma in the distal end of the femur, who underwent reconstruction with a total knee endoprosthesis. The methodology included analysis of signs, symptoms, pathophysiology, complications, physiotherapeutic treatment and information from medical records. Case Report: The patient, diagnosed at the age of 38, went through a complex process, from the discovery of the tumor to surgery to remove the affected bone and implant a total femur and tibia endoprosthesis. The report highlights the evolution, complications and the patient's current dependence to carry out daily activities. Discussion: The increased survival of patients with endoprostheses raises questions about frequent revisions, complications and surgical preferences. The choice between partial and total endoprosthesis is discussed, considering criteria such as age, location and extent of the tumor. Reconstruction of the lower limb with a non-conventional endoprosthesis provides early ambulation, but durability varies. Conclusion: The study concludes that surgical techniques with endoprostheses, whether total or partial, are effective in preventing amputations, improving the quality of life of patients with osteosarcoma. It highlights the importance of physiotherapy in the post-operative period and suggests the need for more studies for early diagnoses, avoiding amputations and promoting better treatments for cancer patients.